Increasing Word Learning Efficiency in Deaf and Hard of Hearing Children Through Retrieval Practice. - McDaniela, Jena (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Despite decades of attempts to "close the gap" between spoken language skills of deaf and hard of hearing (DHH) children and their hearing peers, this goal remains elusive. Retrieval practice is an empirically validated approach that could improve the acquisition and retention of language skills for DHH children. This study evaluates the effectiveness and efficiency of two key features of retrieval practice (feedback and spacing) for learning and retaining novel words. Method: Using a single-case adapted alternating treatments research design, the thirteen 5- to 9-year-old DHH children were divided across four study contrasts. We compare the learning rates for novel words (for expressive, receptive, and semantic performance) under two retrieval practice conditions that differ by the presence of feedback or by spaced versus massed trials and a no-teaching control condition. The 4-week maintenance period permits analysis of retention once mastery is achieved and intervention ends, as is often observed clinically. Results: Results were analyzed based on visual analysis and effect sizes. Nearly all participants learned and retained the novel words for at least one taught word set, which supports the effectiveness of the retrieval practice intervention. For efficiency, learning overall was faster with feedback than without and with spaced trials than massed trials, as predicted. Patterns were similar for expressive, receptive, and semantic outcomes. Conclusions: The findings support use of retrieval practice with direct feedback and spaced trials to increase word learning efficiency for young DHH children. Continued investigation of variation across individuals and learning tasks is warranted.